2019
DOI: 10.1186/s12889-019-7554-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the goal of 12,000 steps per day sufficient for improving body composition and metabolic syndrome? The necessity of combining exercise intensity: a randomized controlled trial

Abstract: Background To investigate the differences in body composition and metabolic syndrome (MS) under a daily 12,000-step strategy with or without moderate-intensity walking exercise in college students with obesity. Methods Thirty-two adults with obesity (mean (s.d.) age: 19.72 (0.80) years; height: 165.38 (3.99) cm; wt: 83.31 (4.66) kg; body mass index: 30.38 (0.83) kg m − 2 ) were recruited and randomly assigned to the walking step goal group (WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations